Dynamics of changes in population immunity to the SARS-CоV-2 virus in residents the Irkutsk region in the context of the COVID-19 pandemic - S. V. Balakhonov; V. I. Dubrovina; A. B. Pyatidesyatnikova; D. D. Briukhova; N. O. Kiseleva; K. M. Korytov; V. V. Voitkova; A. N. Perezhogin; M. V. Chesnokova; T. A. Gavrilova; A. A. Seledtcov (Эпидемиология и вакцинопрофилактика, 2021)
Background. The ongoing COVID-19 pandemic in the world and in Russia remains the main event in 2020. A comprehensive study of the patterns of development and manifestations of the epidemic process of the new coronavirus infection COVID-19 is an urgent line of research. One of the important aspects of the fight against COVID-19 is the study of population immunity to the SARS-CoV-2 virus in order to assess seroprevalence and the formation process of post-infectious humoral immunity to SARS-CoV-2, forecast the development of the epidemiological situation, identify the features of the epidemic process, as well as planning measures for specific and non-specific disease prevention. The aim of the research is to determine the level and structure of population immunity to SARS-CoV-2 among the humans of the Irkutsk region during the COVID-19 epidemic. Materials and methods. As part of the Rospotrebnadzor project to assess population immunity to SARS-CoV-2 in the population of the Russian Federation, research is being conducted among the population of the Irkutsk region in the periods from 06/23/2020 to 07/19/2020 (stage 1), from 09/16/2020 to 09/25/2020 (Stage 2) and from 12/07/2020 to 12/18/2020 (stage 3), taking into account the reacted one recommended by the WHO. The content of antibodies to SARS-CoV-2 was determined by ELISA using a set of tests for human serum or plasma for specific immunoglobulins of class G to the nucleocapsid of the SARS-CoV-2 virus produced by FBUN GNCPMiB Rospotrebnadzor (Obolensk). The results of a research of the humoral immunity of volunteers show that during the period of an epidemic rise in the incidence of COVID-19 in the Irkutsk region, a low level of seroprevalence was formed (stage 1 – 5.8 ± 0.5%, stage 2 – 12,1 ± 0,7%), and in conditions of a long-term maximum increase in the incidence rate ¬– 25,9±1,0% (stage 3). A significant proportion (stage 1 – 81,2±3,2%, stage 2 – 90.9 ±1,9%) of asymptomatic forms of infection characterize the high intensity of the latently developing epidemic process in the first two stages. High levels of IgG in reconvalescents of COVID-19 persisted for an average of 3 to 4.5 months. Conclusion. The results of assessing the population immunity to the SARS-CoV-2 virus in the population of the Irkutsk region indicate that the seroprevalence level at the 3rd stage of the research was 25.9%. After the disease, on average, 41.6% of persons did not detect antibodies. The results obtained should be taken into account when organizing preventive measures, including vaccination, and predicting morbidity.